2013
DOI: 10.3109/13880209.2013.771376
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of liposome-encapsulated anthocyanin on melanogenesis in human melanocytes

Abstract: Context: Melanin plays an important role in preventing ultraviolet (UV) light-induced skin damage. Overexposure to UV radiation can lead to the formation of free radicals and trigger inflammation and hyperpigmentation of the skin. Anthocyanin can combat excessive free radicals in the body and can reduce the occurrence of inflammation. However, anthocyanin molecules are unstable and highly susceptible to degradation. Objective: The present study aims to elucidate the effects of liposome-capsulated anthocyanin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…However, research on the role of encapsulated oligomeric proanthocyanidin in melanogenesis seems to be lacking for the present. However, in another published article, liposome-encapsulated anthocyanin was reported to enhance DPPH scavenging activity and inhibitory effects on melanin production in vitro [21], which partially supports our results that liposome-encapsulated flavonoid LSOPC might still preserve a better related bioactivity.…”
Section: Effects Of Lsopc-nanoliposomes On Diphenolase Activitysupporting
confidence: 90%
“…However, research on the role of encapsulated oligomeric proanthocyanidin in melanogenesis seems to be lacking for the present. However, in another published article, liposome-encapsulated anthocyanin was reported to enhance DPPH scavenging activity and inhibitory effects on melanin production in vitro [21], which partially supports our results that liposome-encapsulated flavonoid LSOPC might still preserve a better related bioactivity.…”
Section: Effects Of Lsopc-nanoliposomes On Diphenolase Activitysupporting
confidence: 90%
“…Catechins, EGCG, and quercetin have all been found to localize in the stratum corneum, viable epidermis and dermis [ 14 , 15 , 18 , 54 ], and these findings have been correlated with their health-promoting properties observed on the skin. Based on the evidence in the literature of similar health benefits of anthocyanins, it seems likely that they will also be preferentially located in these layers [ 6 , 20 , 55 , 56 , 57 ]. However, studies investigating their quantification in the epidermis and dermis, as well as the IC 50 values necessary to exhibit these benefits in vivo, need to be performed.…”
Section: Resultsmentioning
confidence: 99%
“…A study investigated the inhibitory effects of liposome-capsulated anthocyanin (LCA) isolated from Hibiscus sabadariffa Linn . on melanoma development in human A357 melanocytes [ 349 ]. The study demonstrated that anthocyanin with liposome encapsulation increased the stabilization of anthocyanin and the inhibition of melanogenesis.…”
Section: Anthocyanins As Potential Agents For Melanoma Preventionmentioning
confidence: 99%